Keemun black tea: Tracing its narrow-geographic origins using comprehensive elemental fingerprinting and chemometrics. (March 2022) - Ren, Yin-feng; Feng, Can; Ye, Zhi-hao; Zhu, Hai-yan; Hou, Ru-yan; Granato, Daniel; Cai, Hui-mei; Peng, Chuan-yi
Abstract: Authentication of food geographic origin improves traceability, quality control, and brand protection. In this study, elemental fingerprints of 27 mineral elements from 104 samples of Keemun black tea from its core (Qimen) and traditional (Dongzhi and Guichi) production regions were analyzed using inductively coupled plasma - mass spectrometry (ICP-MS) coupled with chemometrics to determine the narrow-geographic origin. Variance analysis revealed that Keemun black teas from different regions had their own elemental fingerprints. Although the orthogonal partial least squares-discriminant analysis (OPLS-DA) presented a satisfactory performance, the discrimination of teas based on linear discriminant analysis (LDA) had 100% accuracy and 99% cross-validation, and thus outperformed OPLS-DA. Similarly, support vector machines was able to differentiate 100% of teas from all geographical origins. The results indicate that elemental fingerprints coupled with chemometrics can be used to authenticate the narrow-geographic origins of Keemun black teas. Highlights: Keemun black teas from narrow-geographic origins were authenticated. Chemometrics was used for authentication of narrow-geographic origin. SVM and LDA were able to differentiate 100% of Keemun black teas. Rb, Ba, Sr, Cu, Zn, Cd, P, Mn, Mo and Ni were important in the classification.